2007
DOI: 10.1103/physrevlett.98.153903
|View full text |Cite
|
Sign up to set email alerts
|

Excitability in a Quantum Dot Semiconductor Laser with Optical Injection

Abstract: Access to the full text of the published version may require a subscription. Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(137 citation statements)
references
References 17 publications
4
132
1
Order By: Relevance
“…We will show later on by using numeric path-continuation techniques that here indeed a saddle-node bifurcation is responsible for the loss of phase-locking. Close to this SNIPER bifurcation, the injected laser has been shown to be excitable [GOU07,KEL09,KEL11]. This can be understood by the close distance of the stable node and the saddle in phase-space.…”
Section: Injection Locking Of Quantum-dot Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…We will show later on by using numeric path-continuation techniques that here indeed a saddle-node bifurcation is responsible for the loss of phase-locking. Close to this SNIPER bifurcation, the injected laser has been shown to be excitable [GOU07,KEL09,KEL11]. This can be understood by the close distance of the stable node and the saddle in phase-space.…”
Section: Injection Locking Of Quantum-dot Lasersmentioning
confidence: 99%
“…When the frequency of the injected signal is too large, the beating between the external and cavity fields can induce nonlinear oscillations [TRE85] as well as deterministic chaos [SIM94a], multi-stability [GAV97], or excitability close to the boundary of phase-locking [GOU07]. Apart from their scientific appeal, these nonlinear dynamics can also be exploited and used for technological applications.…”
Section: Quantum-dot Laser Dynamicsmentioning
confidence: 99%
“…In [10] the optical injection properties of a multimode QD laser were reported. There it was shown that for low to moderate injection strengths, fast dynamics can be observed close to the locking boundary for negative detuning.…”
Section: Methodsmentioning
confidence: 99%
“…A particularly attractive property is an unusually high damping of the ROs [18] in comparison to their bulk and quantum well (QW) counterparts. This high damping has been cited as the principal reason for the increased stability of such devices subject to optical feedback [21], optical injection [8,10,14], and mutual coupling [12,15] configurations. We determine here an experimental stability diagram with the injection strength and the detuning as control parameters and note that it is considerably different from that of a conventional QW laser.…”
Section: Introductionmentioning
confidence: 99%
“…1 that for the moderate bias current density j = 3j th , without detuning and with the injected optical power P opt ∼ 1mW the QD and QW carrier pulses are synchronized. The numerical simulations show that for larger bias current densities of (5 − 6) j th , the detuning of 1−5 GHz, and the injected optical power up to 3−4mW , the switching in the turn-on regime is accompanied by the rapid oscillations of the QDWELL laser output photon density which corresponds to the experimental results [5].…”
Section: Simulation Resultsmentioning
confidence: 83%